Application of Nanoscaffolds in Mesenchymal Stem Cell-Based Therapy. (23rd September 2014) - Ghoraishizadeh, Saman; Ghorishizadeh, Afsoon; Ghoraishizadeh, Peyman; Daneshvar, Nasibeh; Boroojerdi, Mohadese Hashem
Abstract : Regenerative medicine is an alternative solution for organ transplantation. Stem cells and nanoscaffolds are two essential components in regenerative medicine. Mesenchymal stem cells (MSCs) are considered as primary adult stem cells with high proliferation capacity, wide differentiation potential, and immunosuppression properties which make them unique for regenerative medicine and cell therapy. Scaffolds are engineered nanofibers that provide suitable microenvironment for cell signalling which has a great influence on cell proliferation, differentiation, and biology. Recently, application of scaffolds and MSCs is being utilized in obtaining more homogenous population of MSCs with higher cell proliferation rate and greater differentiation potential, which are crucial factors in regenerative medicine. In this review, the definition, biology, source, characterization, and isolation of MSCs and current report of application of nanofibers in regenerative medicine in different lesions are discussed.